2020
DOI: 10.1111/1365-2435.13502
|View full text |Cite
|
Sign up to set email alerts
|

The role of biotic interactions in determining metal hyperaccumulation in plants

Abstract: Heavy metal hyperaccumulation (MH) is a rare trait found in plant species that inhabit metal‐contaminated soils. Two main hypotheses proposed to explain the selective advantage of MH are the elemental defence hypothesis and elemental allelopathy hypothesis. The elemental defence hypothesis suggests that MH functions as defence against herbivores while the elemental allelopathy hypothesis suggests that MH acts to inhibit the growth of neighbours. Nevertheless, these hypotheses are not likely to be mutually excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
12
0
2
Order By: Relevance
“…This suggests a tradeoff between interspecific competitive ability and metal accumulation (Ernst et al, 1992); the sequestration of metal in the plant could incur a cost that would not allow larger species to reach reproductive maturity in a short growing season. However, this result could also support the idea that leaf metal accumulation is a mechanism of biotic interaction (allelopathy) that would benefit poorly competitive, small species (Mohiley, Tielbörger, Seifan, & Gruntman, 2020). There were only moderate interspecific correlations between leaf metal concentrations and LES traits, potentially indicating that the physiological mechanisms required for metal tolerance within the leaves do not interact with resources use.…”
Section: Functional Traits Integration In Metallophytessupporting
confidence: 54%
“…This suggests a tradeoff between interspecific competitive ability and metal accumulation (Ernst et al, 1992); the sequestration of metal in the plant could incur a cost that would not allow larger species to reach reproductive maturity in a short growing season. However, this result could also support the idea that leaf metal accumulation is a mechanism of biotic interaction (allelopathy) that would benefit poorly competitive, small species (Mohiley, Tielbörger, Seifan, & Gruntman, 2020). There were only moderate interspecific correlations between leaf metal concentrations and LES traits, potentially indicating that the physiological mechanisms required for metal tolerance within the leaves do not interact with resources use.…”
Section: Functional Traits Integration In Metallophytessupporting
confidence: 54%
“…Specifically, we asked if responses to herbivory differ between plants from metalliferous versus non-metalliferous origin. A. halleri from both these origins have been shown to hyperaccumulate Cd [ 19 , 22 , 23 ]. However, results from a previous study with the same genotypes used in this study showed that A. halleri from a non-metalliferous origin are less tolerant to high concentrations of Cd in their tissues and showed markedly reduced growth when grown in Cd-rich soils, while plants from metalliferous soil were not affected [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of such plant species can be found in the Brassicaceae family that hyperaccumulate heavy metals such as zinc (Zn), cadmium (Cd) or nickel (Ni) up to 100-1000-fold higher than those found in non-hyperaccumulating species [15]. Several hypotheses have been suggested to explain why such behaviour could be beneficial, and the most common is the elemental defence hypothesis, which suggests that heavy metals could serve as herbivore defence [16][17][18][19]. Interestingly, some metal-hyperaccumulating plants have been shown to forage for heavy metals [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example for such plants are metal hyperaccumulating species, which actively uptake excessive concentrations of heavy metals into their aboveground tissues (Krämer 2010). Metal hyperaccumulation has been found to be important as herbivore defence (the elemental defence hypothesis: Kazemi-Dinan et al 2014;Plaza et al 2015) as well as provide plants with allelopathic abilities (the elemental allelopathy hypothesis: Morris et al 2009;Mohiley et al 2020). Allelopathic effects could be conveyed in these plants when their metal-enriched leaves are shed, and as a result increase the heavy metal concentration around them and inhibit the germination and growth of metal sensitive neighbouring species (Boyd and Jaffré 2001;El Mehdawi et al 2011Jaffe et al 2018).…”
Section: Introductionmentioning
confidence: 99%